Productive chains in Southeast Asia: integration to global networks with local companies (2015)
The article presents an overview of industrial policies in Southeast Asia and their implications in the formation of economic agglomerations and the linking of local companies in international production processes. The different forms of assimilation of capitalism in the region and the trajectories of industrialization that determine its link with international capital stand out. Singapore stands out as a success story in the insertion into the international production process thanks to its industrial policy. In the extreme case, Thailand also set out to develop industrial clusters to attract capital and develop national industry, but nationalist policies and economic concentration inhibited that purpose. Malaysia and Vietnam are intermediate cases of success in taking advantage of international production chains and networks, but they must still promote ways to develop their own technology that allows them to reduce dependence on transnational corporations. The main challenge of these countries is the formation of human capital to integrate into the stages of value creation and avoid the disadvantages of the fragmentation of global capitalism.